Nucleoside Transport Inhibition by Dipyridamole Prevents Angiogenesis Impairment by Homocysteine and Adenosine - Antony Kam; Valentina Razmovski-Naumovski; Xian Zhou; John Troung; Kelvin Chan (Frontiers Media S.A., 2015)
Purpose: Adenosine plays an important role in the pathogenesis of homocysteine-associated vascular complications. Methods: This study examined the effects of dipyridamole, an inhibitor for nucleoside transport, on impaired angiogenic processes caused by homocysteine and adenosine in human cardiovascular endothelial cell line (EAhy926). Results: The results showed that dipyridamole restored the extracellular adenosine and intracellular S-adenosylhomocysteine concentrations disrupted by the combination of homocysteine and adenosine. Dipyridamole also ameliorated the impaired proliferation, migration and formation of capillary-like tubes of EAhy926 cells caused by the combination of homocysteine and adenosine. Mechanism analysis revealed that dipyridamole induced the phosphorylation of mitogen-activated protein kinase kinase (MEK) and extracellular signal-regulated kinases (ERK) and its effect on cell growth was attenuated by the MEK inhibitor, U0126. Conclusion: Dipyridamole protected against impaired angiogenesis caused by homocysteine and adenosine, at least in part, by activating the MEK/ERK signalling pathway, and this could be associated with its effects in suppressing intracellular S-adenosylhomocysteine accumulation. Novelty of the Work: This is the first paper showing that nucleoside transport inhibition by dipyridamole reduced impaired angiogenic process caused by homocysteine and adenosine. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.